Towards an Inclusive Pluralism: A Constructive Assessment of John Macquarrie's Natural Theology and John Cobb's Process Theology - Bloostein, Eitan R. (Tufts Archival Research Center, 2019)
This thesis analyzes the theological work of John Macquarrie, with a focus on his natural theology, and the work of John Cobb, with a focus on his process theology, to understand how these thinkers understand other religions. It critiques both thinkers and offers a constructive position which Christian theologians can take on this issue. Advisor: Professor Elizabeth Lemons